ELITE THEORY OF VILFREDO PARETO - Akramov Khasan; Kuchkarova K. X. (Web of Journals Publishing, 2024)
This article provides a comprehensive analysis of the “elite theory”, considered the closest theory of Vilfredo Pareto to sociology. What this theory is about, the differences between the elite and the lower tier, their tasks,role are covered. The role and how consistent the theory Pareto created at the time and in the present has been studied. Can representatives of the lower tier also rise to the elite? How does the elite manage society? The answer to similar questions is explained.
Keywords: Vilfredo Pareto, elite, elite theory, elite circulation, rulers, lower tier, management, subordinate.